The Under- and Over-Identification of Autism: Factors Associated With Diagnostic Referral. Issue 3 (4th May 2019) - Smith, Isaac C.; Swain, Deanna; Murphy, Haley G.; Ollendick, Thomas H.; White, Susan W.
Abstract : As reported prevalence and public awareness of Autism Spectrum Disorder (ASD) have grown in recent years, clinicians will likely see increased referrals for suspected ASD. The current study sought to elucidate factors associated with referral for possible ASD, as well as diagnostic outcome among youth referred for suspected ASD. Youth referred for psychological evaluations at an outpatient clinic ( N  = 69, 6–18 years, 48 male) were categorized into four groups: referred for suspected ASD and diagnosed as such, referred for ASD and not diagnosed as such, not referred for ASD but diagnosed as such, and neither referred for nor diagnosed with ASD. Approximately half of cases referred for suspected ASD did not meet diagnostic criteria. A significant effect of group was found for cognitive ability and anxiety. Youth receiving ASD diagnoses, regardless of whether they were referred for suspected ASD, demonstrated lower cognitive ability than children not receiving ASD diagnoses. Youth neither referred for nor diagnosed with ASD demonstrated lower anxiety than those who were referred and diagnosed. Maternal education significantly differed among the four groups. Although group differences are seen for youth cognitive ability, anxiety, and maternal education, we found no clear indicators differentiating referrals that were "accurate" (i.e., those diagnosed with ASD) and those that were not (i.e., those who did not receive ASD diagnosis). Comorbidity was high in all groups, including those referred primarily for ASD assessment, underscoring the importance of comprehensive assessment regardless of specificity of the referral.